Evaluasi Efektivitas Program Rumah Padat Karya dalam Upaya Penanggulangan Kemiskinan Berkelanjutan di Kota Surabaya - Nur Fadila, Aisyah; Ellya Roziana, Norma; Chauliya Nadina Putri, Rayshya; Muharwati, Marini; Naufarezi, Rayhan; Tauran; Sumarsyah, Wilda (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The Rumah Padat Karya Program in Surabaya City is one of the local government policies to reduce poverty through job creation and empowerment of low-income communities (MBR). This study aims to evaluate the effectiveness of the Rumah Padat Karya Program in reducing poverty rates in Surabaya and to assess its alignment with the Sustainable Development Goals (SDGs), particularly Goal 1 (No Poverty), Goal 8 (Decent Work and Economic Growth), and Goal 11 (Sustainable Cities and Communities). The study employs a formal evaluation approach with a formative evaluation type, given that the program is still ongoing. Data were collected through interviews, observation, and documentation, and analyzed qualitatively. The evaluation was conducted using William N. Dunn’s (2003) criteria, comprising effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The results indicate that the program is fairly effective in reducing poverty and unemployment through local workforce absorption and the productive utilization of previously idle government assets. However, limitations remain, including budget constraints, inter-district facility disparities, weak inter-agency coordination, and suboptimal business mentoring and market access. Therefore, it is necessary to strengthen the mentoring system, equalize facilities, and enhance cross-sector collaboration so that the program can run more optimally and sustainably.